(untitled) (The South Asianist Journal, 2015)
The partitioning of British India in August 1947 into its principal successor state, Hindu-majority India, and newly formed Muslim-majority Pakistan, like many of the now infamous partitions of the twentieth century, did not take place without considerable humanitarian turmoil. Indeed a communal genocide of provincial and district minority populations, together with a huge transfer of population to and fro the two dominions, preceded, accompanied and followed the official Partition. This paper focuses upon the ‘memory’ of this episode as held by one of its participant groups—the Sikh refugees—who migrated from the territory of prospective/realised West Pakistan into truncated India. This paper contends that the Sikh refugees have sought to convey, through their memory of this episode, that ‘their people’ were the foremost victims of Partition. This is both in terms of the associated violence and the long-term material consequences deriving from being driven out of their ‘homelands’.